The Branding of the Islamic Sharia Image in Aceh - Azman Sulaiman; Lahmuddin Lubis; Zulkarnain Abdurrahman (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
The implementation of Islamic law in Aceh has been formally enforced for more than two decades, yet its image remains dominated by negative public perceptions. In fact, the enforcement of Islamic law in Aceh is necessary for the Acehnese people, who have undergone a long, dynamic process between Aceh and the central government. This study aims to analyze the branding of the image of Islamic law in Aceh to formulate effective communication strategies to support the strengthening of its implementation. This study uses a mixed-method approach, combining a quantitative survey to capture public perceptions with a qualitative approach through in-depth interviews and focus group discussions. Berger and Luckmann’s social construction theory serves as an analytical framework for understanding the process of forming and negotiating the meaning of Islamic Sharia. The results of the study show that negative perceptions of Islamic Sharia are influenced by weak coordination between institutions, inequality in law enforcement, and resistance from some community groups. However, it was also found that local culture plays a vital role in internalizing the values of Sharia and strengthening its positive image as the religious and cultural identity of the Acehnese people.